Survey of Five Athletic Academic Support Facilities - Ferris, Ellen (My University, 1987)
A survey of academic study facilities was conducted to answer the basic questions: what is the facility used for, who uses the facility, when is the facility used, and what are the primary benefits of having such a facility for the student-athletes. The author surveyed directors from Georgia Tech, Minnesota, SMU, UNC, and Kentucky. Responses are provided in tables.
Keywords: facilities; staff; budgets; Division I